Extraction and Potential Use of Black Pepper (Piper Nigrum) Oil as Attractant for Bactrocera Dorsalis - Dela Cruz, Louise Raphaelle; Sarno, Mormie Joseph; Mercado, Giovani; Pajarito, Dexter; Galang , Myrnille Joy; Garduque, Viola (12th International Scholars Conference 2025, 2026)
Mango is considered one of the most valued crops in the Philippines. However, the production of quality mango fruit has been declining due to various environmental factors, inflated cost of production, and severe pest infestations. One of the most damaging pests in the mango industry is Bactrocera dorsalis, commonly known as Oriental fruit fly, which affects the fruit quality and reduces its market value and export potential. Investigation of the effectiveness of black pepper oil as an attractant for mass trapping of B. dorsalis was the aim of this research, since the commercially available lures only target a specific sex of fruit flies. In this research, steam distillation and Soxhlet extraction using two solvents, hexane and ethanol, were used to extract volatiles and essential oils from dried black pepper. The attractancy of fruit flies to the extracted oils was tested using a controlled environment setup. Hexane black pepper oil (BPO) extract obtained the highest number of trapped fruit flies, while BPO from steam distillation showed minimum attractiveness to B. dorsalis. A multi-choice test bioassay showed that the attractiveness of hexane BPO extract was comparable to that of commercially used attractants in the market. These findings suggested a possible use of black pepper oil as an alternative attractant for B. dorsalis control.